Between-group Competition in the Labor Market and the Rising Returns to Skill: US and France 1964-2000 - Etienne Wasmer (Institute for the Study of Labor (IZA), 2001)
This paper describes the changes in the composition of the labor force in the last 35 years and quantifies the substitution of low education / high experience workers by low experience / high education workers by using US and French microdata. The consequences of this substitution on the wage structure are then investigated. In the US, labor supply changes can explain the changes in returns to experience. It also accounts for a part of the increase in returns to education between 1980 and 2000, between 8% and 20% depending on the specification. These results rely on panel estimates of a useful concept: the elasticity of substitution between experience and education, which is found to be less than half. In France, the covariations of prices and the supply of skills are consistent with a pure labor supply explanation. Methodologically, the paper shows that the use of a stock measure of efficient units of skills is better than flow measures (e.g. cohort size). It also allows to analyze the consequences of rising female labor participation.
Keywords: E34; J31; J21; 330; Wage inequality; education; experience; labor supply; Arbeitsmarkt; Qualifikation; Einkommensverteilung; Lohnstruktur; Bildungsertrag; Vergleich; Frankreich; USA; Berufserfahrung